Subprime borrowers, securitization and the transmission of business cycles - Anna Grodecka (Sveriges Riksbank, 2016)
A growing literature (i.e. Jaffee, Lynch, Richardson, and Van Nieuwerburgh, 2009, Acharya and Schnabl, 2009) argues that securitization improves financial stability if the securitized assets are held by capital market participants, rather than financial intermediaries. I construct a quantitative macroeconomic model with a novel specification for mortgage-backed securities (MBS) to evaluate this claim for subprime securitization during the Great Recession. I find that output in the U.S. would have dropped by only about a third and house prices by only a half of what we actually observed, if subprime MBS had been purchased by non-financial agents, rather than held by banks. This is because banks are subject to capital requirements and if MBS remain within the banking system, the fall in their value puts a strain on banks' balance sheets. The subsequent deleveraging amplifies business cycles. My findings suggest that the existence of the securitization market stabilizes the economy under the condition that financial intermediaries do not engage in the acquisition of securitized assets.
Keywords: E32; E44; G01; G13; G21; R21; 330; Subprime Borrowers; Securitization; Financial Intermediation; Great Recession